The influence mechanism of radiation shielding functional ceramsite on the performance and microstructure of UHPC - Jun Yang; Jianyu Li; Gaozhan Zhang; Peng Zhou; Qingjun Ding; Mingming Wu (Case Studies in Construction Materials)
With the widespread application of nuclear energy technology, there is a growing demand for radiation-shielding building materials. Ultra-high-performance concrete (UHPC) stands out among many building materials for its superior mechanical properties and durability, but the issues of its significant shrinkage and insufficient radiation-shielding performance remain unresolved. This study explores the impact of radiation-shielding functional aggregate (RSFA), a form of barium aluminosilicate ceramsite, on the mechanical properties, durability, and microstructure of UHPC. The shielding effectiveness against gamma and neutron radiation was evaluated using the XCom program. The results show that the mechanical properties of UHPC decreases with the substitution of RSFA for ilmenite sand. When the replacement of RSFA is 70 %, the strength of UHPC can still reach 121.2 MPa. The addition of RSFA enhances chloride resistance, carbonation resistance, and impermeability. Microstructural analysis revealed that the interfacial transition zone (ITZ) around RSFA exhibits a dense structure with superior micro-mechanical properties. At a replacement level of 50 %, RSFA effectively demonstrates its internal curing effects. The gamma-ray shielding performance of UHPC decreases with the incorporation of RSFA, which can be predicted through XCom calculations. The neutron shielding performance of UHPC is enhanced by the addition of RSFA. However, the effective neutron removal cross-section calculations and experimental results yielded opposing outcomes, indicating that the neutron absorption behavior of UHPC is complex and requires further research.